The Queer Cultural Work of Lily Tomlin and Jane Wagner - Reed, J. author. aut Link
XI, 191 p. 11 illus.
Keywords: Lily Tomlin and Jane Wagner have been partners in life and work for more than 40 years. Over those years they have been comedic pioneers in television, sound recording, film, theater, and animation. This book explores the ways they have used and expanded notions of queer to make their unique impact on American culture.